Bilateral transfer of motor performance as a function of motor imagery training: a systematic review and meta-analysis - Wan X. Yao; Sha Ge; John Q. Zhang; Parisa Hemmat; Bo Y. Jiang; Xiao J. Liu; Xing Lu; Zayd Yaghi; Guang H. Yue; Guang H. Yue (Frontiers in Psychology, 2023)
ObjectiveThe objective of this review was to evaluate the efficacy of mental imagery training (MIT) in promoting bilateral transfer (BT) of motor performance for healthy subjects.Data sourcesWe searched 6 online-databases (Jul-Dec 2022) using terms: “mental practice,” “motor imagery training,” “motor imagery practice,” “mental training,” “movement imagery,” “cognitive training,” “bilateral transfer,” “interlimb transfer,” “cross education,” “motor learning,” “strength,” “force” and “motor performance.”Study selection and data extractionWe selected randomized-controlled studies that examined the effect of MIT on BT. Two reviewers independently determined if each study met the inclusion criteria for the review. Disagreements were resolved through discussion and, if necessary, by a third reviewer. A total of 9 articles out of 728 initially identified studies were chosen for the meta-analysis.Data synthesisThe meta-analysis included 14 studies for the comparison between MIT and no-exercise control (CTR) and 15 studies for the comparison between MIT and physical training (PT).ResultsMIT showed significant benefit in inducing BT compared to CTR (ES = 0.78, 95% CI = 0.57–0.98). The effect of MIT on BT was similar to that of PT (ES = –0.02, 95% CI = –0.15–0.17). Subgroup analyses showed that internal MIT (IMIT) was more effective (ES = 2.17, 95% CI = 1.57–2.76) than external MIT (EMIT) (ES = 0.95, 95% CI = 0.74–1.17), and mixed-task (ES = 1.68, 95% CI = 1.26–2.11) was more effective than mirror-task (ES = 0.46, 95% CI = 0.14–0.78) and normal-task (ES = 0.56, 95% CI = 0.23–0.90). No significant difference was found between transfer from dominant limb (DL) to non-dominant limb (NDL) (ES = 0.67, 95% CI = 0.37–0.97) and NDL to DL (ES = 0.87, 95% CI = 0.59–1.15).ConclusionThis review concludes that MIT can serve as a valuable alternative or supplement to PT in facilitating BT effects. Notably, IMIT is preferable to EMIT, and interventions incorporating tasks that have access to both intrinsic and extrinsic coordinates (mixed-task) are preferred over those that involve only one of the two coordinates (mirror-task or normal-task). These findings have implications for rehabilitation of patients such as stroke survivors.